Spekulasi, Speculation, Speculationem - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Abstraksi Energy crisis has dampened the world economy especially in developing countries. Real sectors faced the reality of rising fuel price thus increasing production prices that led to inflation. Many researchers investigated the triggers of energy crisis. Many factors arose with the fundamental of demand and supply of oil as the main reason behind the crisis. But the market witnessed extreme changes of oil prices even tough demand and supply factor is not significant to explain those changes in oil prices. Many turned their attention to non-fundamental factor, the so called speculation. Speculation was believed to drive the oil prices to a new record high. The paper analyzed whether speculation affects the changes in oil prices. Keyword: crisis, specu lation, behavior